Penerapan Teknologi Pembuatan Pakan Ternak Ruminansia di Desa Teluk Santong Kecamatan Plampang Kabupaten Sumbawa - Muhamad Amin; Syamsul Hidayat Dilaga; Dahlanuddin Dahlanuddin; Oscar Yanuarianto; Azhary Noersidiq (Jurnal Gema Ngabdi, 2026)
This community service activity was conducted to address the problem of feed scarcity faced by farmers in Teluk Santong Village, Plampang Subdistrict, Sumbawa Regency, especially during the dry season. The main issue was the limited knowledge and skills of farmers in utilizing abundant agricultural waste, such as rice straw and corn straw, as a quality feed source. The objective of this program was to enhance the farmers' capacity in feed processing through the application of ammoniation and fermentation technologies. The implementation method involved three stages: counseling through lectures, distribution of written materials (brochures), and direct hands-on demonstration with the "Putra Ano Siup" Farmer Group. The results showed high enthusiasm from the participants, who actively engaged in discussions and practice. The farmers successfully adopted the introduced technologies and are now able to independently produce processed feed. This activity has provided a practical and sustainable solution to ensure the year-round availability of quality feed, thereby supporting livestock productivity in the region. Based on the positive response and the successful adoption of the technology, this program was considered successful